Physicians' patient base composition and mortality among people living with HIV who initiated antiretroviral therapy in a universal care setting. Issue 3 (20th March 2019) - Allan, Beverly; Closson, Kalysha; Collins, Alexandra B; Kibel, Mia; Pan, Shenyi; Cui, Zishan; McLinden, Taylor; Parashar, Surita; Lima, Viviane Dias; Chia, Jason; Yip, Benita; Barrios, Rolando; et al.
Abstract : Objectives: To assess the impact of physicians' patient base composition on all-cause mortality among people living with HIV (PLHIV) who initiated highly active antiretroviral therapy (HAART) in British Columbia (BC), Canada. Design: Observational cohort study from 1 January 2000 to 31 December 2013. Setting: BC Centre for Excellence in HIV/AIDS' (BC-CfE) Drug Treatment Program, where HAART is available at no cost. Participants: PLHIV aged ≥ 19 who initiated HAART in BC in the HAART Observational Medical Evaluation and Research (HOMER) Study. Outcome measures: All-cause mortality as determined through monthly linkages to the BC Vital Statistics Agency. Statistical analysis: We examined the relationships between patient characteristics, physicians' patient base composition, the location of the practice, and physicians' experience with PLHIV and all-cause mortality using unadjusted and adjusted Cox proportional hazards models. Results: A total of 4 445 PLHIV (median age = 42, Q1, Q3 = 34–49; 80% male) were eligible for our study. Patients were seen by 683 prescribing physicians with a median experience of 77 previously treated PLHIV in the past 2 years (Q1, Q3 = 23–170). A multivariable Cox model indicated that the following factors were associated with all-cause mortality: age (aHR = 1.05 per 1-year increase, 95% CI = 1.04 to 1.06), year of HAART initiation (2004–2007: aHR = 0.65, 95% CI = 0.53 to 0.81, 2008-2011: aHR = 0.46, 95% CI = 0.35 to 0.61, Ref: 2000–2003), CD4 cell count at baseline (aHR = 0.88 per 100-unit increase in cells/mm 3, 95% CI = 0.82 to 0.94), and < 95% adherence in first year on HAART (aHR = 2.28, 95% CI = 1.88 to 2.76). In addition, physicians' patient base composition, specifically, the proportion of patients who have a history of injection drug use (aHR = 1.11 per 10% increase in the proportion of patients, 95% CI = 1.07 to 1.15) or Indigenous ancestry (aHR = 1.07 per 10% increase, 95% CI = 1.03–1.11) and being a patient of a physician who primarily serves individuals outside of the Vancouver Coastal Health Authority region (aHR = 1.22, 95% CI = 1.01 to 1.47) were associated with mortality. Conclusions: Our findings suggest that physicians with a higher proportion of individuals who face potential barriers to care may need additional supports to decrease mortality among their patients. Future research is required to examine these relationships in other settings and to determine strategies that may mitigate the associations between the composition of physicians' patient bases and survival.